2015
DOI: 10.1177/1471301215618570
|View full text |Cite
|
Sign up to set email alerts
|

Predicting perceived medication-related hassles in dementia family caregivers

Abstract: Objective This study examined predictors of medication administration hassles reported by intergenerational dementia family caregivers. Methods A sample of 53 women who aided a cognitively impaired older adult with healthcare and who identified as inter-generational caregivers provided self-report medication management and psychosocial data. Results Hierarchical multiple regression analyses revealed that six independent variables hypothesized for this model, the total number of prescription medications managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Schmidt et al 26 reported that almost an equal proportion of 152 caregivers were involved in decisions about dosages (80.9%) as they were involved in decisions to initiate/cease medications (80.3%). This finding was similarly reported by George and Steffen, who found that most caregivers in the study were involved in decisions regarding dosage changes (83.0%) and in initiating/ceasing medications for the person living with dementia (86.8%) 21 . Travis et al reported a correlation between increased complexity in medication selection (medication‐related decision‐making) and increased caregiver burden in medication management, which was indicated by elevated Hassles and Medication Complexity Index scores (Medication Complexity Index, r = .19, p = .05; Hassles Caregiver Strain Index, r = .44, p = .01) 27 .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Schmidt et al 26 reported that almost an equal proportion of 152 caregivers were involved in decisions about dosages (80.9%) as they were involved in decisions to initiate/cease medications (80.3%). This finding was similarly reported by George and Steffen, who found that most caregivers in the study were involved in decisions regarding dosage changes (83.0%) and in initiating/ceasing medications for the person living with dementia (86.8%) 21 . Travis et al reported a correlation between increased complexity in medication selection (medication‐related decision‐making) and increased caregiver burden in medication management, which was indicated by elevated Hassles and Medication Complexity Index scores (Medication Complexity Index, r = .19, p = .05; Hassles Caregiver Strain Index, r = .44, p = .01) 27 .…”
Section: Resultssupporting
confidence: 87%
“…Study designs included cross‐sectional studies ( n = 8), unblinded randomized‐controlled trials ( n = 1) and mixed‐methods studies ( n = 1), with sample size ranging from 53 to 1369 participants (Table 1). Only 1 22 out of the 10 included studies reported the stage of dementia diagnosis for their participants 5,21–29 . Medication selection was an aspect of medication management reported in 6 out of 10 studies, 21,23,26–29 supply 5,21,23,24,26–28 and monitoring/review 5,22,23,25–27,29 was captured in seven studies and administration was reported in nine studies 5,21–28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Saifi and colleagues’ (2018) study, which also focuses on informal caregivers, examines one of the most complicated, yet largely understudied, responsibilities of family caregivers of persons with dementia – securing appropriate medication adherence (George and Steffen, 2017). While previous studies have examined caregivers’ characteristics, associated with their own medication adherence (Wang et al , 2015), to the best of my knowledge, this is the first study to assess caregivers’ factors associated with care-receivers’ medication adherence.…”
Section: Overview Of the Papers In This Issuementioning
confidence: 99%